Strategi Guru Dalam Meningkatkan Motivasi Menghafal Al-Qur’an Pada Program Tahfidz di SD Islam Al-Azhaar Tulungagung - Afifah Azizatul Fauziah (The Elementary Journal, 2023)
This research is motivated by the existence of the tahfidz program which is increasingly being implemented in Islamic educational institutions, including at Al-Azhaar Islamic Elementary School Tulungagung. One of the successes of students memorizing the Qur'an is determined by the teacher's strategies such as learning methods, learning media, and learning evaluations that are specially prepared to improve the memorization. Besides that, teachers also need to foster students' motivation to memorize the Qur'an. The purpose of this study is to describe methods, learning media, and teacher evaluations in increasing motivation to memorize the Qur'an in the Tahfidz program at Al-Azhaar Islamic Elementary School Tulungagung. This type of qualitative research. Data collection tools using observation, interviews, and documentation. Data analysis uses data reduction, data presentation, and drawing conclusions. The results of the study are as follows: (1) The method used by the teacher is using the talaqqi, Bin-Nazar, talqin method, which is accompanied by the provision of advice and motivation. (2) The learning media used to increase motivation to memorize the Qur'an using audio-visual media that is played is the reading of the Qur'an of the Shaykhs. Become the right medium for memorizing the Qur'an. (3) Teacher evaluation in Improving Motivation to Memorize Al-Qur'an which consists of formative evaluation and summative evaluation. Formative evaluation to test the memorization of 1 surah, a quarter juz or half a juz. While the summative evaluation is to test the student's memorization of 1 juz.